2018
DOI: 10.3390/en11113118
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Feasibility Study of a Hypersaline Pressure-Retarded Osmosis Power Plants: Dead Sea–Red Sea Conveyor

Abstract: In this study, three pressure retarded osmosis (PRO) power plants are proposed to be built on the Red Sea–Dead Sea (RSDS) water conveyance project, to generate power from the salinity gradient between two water streams at different salt concentrations. The first two proposed plants are to be built after sea water reverse osmosis (SWRO) desalination plants, where Red Sea water and the rejected brine from SWRO plants are used as feed and draw solutions, respectively. In the third proposed plant, Red Sea water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A LCOE between 0.62–0.97 $ per kW h is estimated for feed water of different salinities. Based on the analysis model, suggestions including waste water treatment (as feed water) or PRO installation near waste water source (within 1 km) could effectively reduce the LCOE down to 0.14 $ per kW h. Khasawneh et al 157 analyzed the feasibility of installing PRO power plants with Red Sea-Dead sea waters. It was demonstrated that the project is technically and economically feasible, with a LCOE of 0.056 $ and a power of 134.5 MW.…”
Section: Osmotic Energy Harvestingmentioning
confidence: 99%
“…A LCOE between 0.62–0.97 $ per kW h is estimated for feed water of different salinities. Based on the analysis model, suggestions including waste water treatment (as feed water) or PRO installation near waste water source (within 1 km) could effectively reduce the LCOE down to 0.14 $ per kW h. Khasawneh et al 157 analyzed the feasibility of installing PRO power plants with Red Sea-Dead sea waters. It was demonstrated that the project is technically and economically feasible, with a LCOE of 0.056 $ and a power of 134.5 MW.…”
Section: Osmotic Energy Harvestingmentioning
confidence: 99%
“…The salt gradient energy can be exploited by several technologies such as pressure retarded osmosis (PRO) and reverse electrodialysis (RED). A unique application of SWRO‐PRO is demonstrated in a case study which proposes combining three PRO plants with two SWRO plants on the Red Sea–Dead Sea (RSDS) water conveyance project (Khasawneh et al., 2018). Although only the concentrate generated from desalination is considered in this overview, every industry producing concentrates should be looking into recovering available resources from those concentrates.…”
Section: Sustainable Use Of Resourcesmentioning
confidence: 99%